Development of Trends in Russian-Mongolian Educational Cooperation in New Conditions - O. A. Beregovaya; A. S. Bobrova; M. A. Yurchenko (Дискурс, 2023)
Introduction. The article is devoted to the problem of international relations in the field of higher education. The purpose of the study is to consider the development of modern Russian-Mongolian educational cooperation. The authors set the following objectives of the article: to reveal the role of the Russian language as one of the tools for the development of Russian-Mongolian educational cooperation; to enumerate and describe the features of the promotion of Russian higher education in Mongolia; to illustrate the experience of developing Russian-Mongolian educational cooperation on the example of Novosibirsk universities.Methodology and sources. The study of the problem of international cooperation in the field of higher education is based on a socio-cultural approach. The methodological basis is the concept of education as a «soft power». The study is conducted with the use of the following sociological methods: the focus group-method; analysis of secondary sociological research; comparison; generalization. The sources of the study are the regulatory documents on which Russian-Mongolian relations are based as well as data from other studies on the topic.Results and discussion. Based on the data obtained, the researchers come to the conclusion about positive trends in educational cooperation, however, the potential of Russian-Mongolian relations is not fully realized. After the pandemic, more active promotion of Russian educational programs in Mongolia is needed, which will allow updating approaches to Russian-Mongolian cooperation in the field of higher education. The article offers a list of measures for the development of Russian-Mongolian cooperation, including the development of intercultural communication and dialogue between Russian and Mongolian students.Conclusion. Based on the data obtained, the researchers came come to the conclusion about positive trends in educational cooperation, however, the potential of Russian-Mongolian relations is not fully realized. After the pandemic, more active promotion of Russian educational programs in Mongolia is needed, which will allow updating approaches to Russian-Mongolian cooperation in the field of higher education. The article offers a list of measures for the development of Russian-Mongolian cooperation, including the development of intercultural communication and dialogue between Russian and Mongolian students.